The Rentak Kapuas Dance: A Representation of the Social Values of the People of Pontianak City - Ismunandar, Ismunandar (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
The Rentak Kapuas Dance is a traditional dance from West Kalimantan that reflects the spirit of the people in living life. This dance combines traditional Malay and Dayak movements that have been developed to be more interesting and dynamic. Fan props are used to symbolize water and rivers, and depict the siluk fish or arowana, icons of West Kalimantan that symbolize splendor and prosperity. This dance has agile and energetic movements, symbolizing the spirit and tenacity of the people of West Kalimantan in facing life. The Rentak Kapuas Dance combines elements of soft Malay dance with more expressive and powerful Dayak dance movements. Some versions of this dance use fans as the main prop, symbolizing water and the Kapuas River as the source of life. Dance movements are often inspired by the surrounding nature, including the movement of water, fish, and other elements that represent local wisdom. It is usually accompanied by traditional musical instruments such as Malay drums, gambus, and Dayak musical instruments to create a unique West Kalimantan atmosphere. The Rentak Kapuas Dance is not just entertainment, but also has a deep philosophy about togetherness, prosperity, and harmony in life. This dance depicts how people from different backgrounds can live.